2019
DOI: 10.1080/17445647.2019.1663282
|View full text |Cite
|
Sign up to set email alerts
|

Plants and animals in the oikonyms of Lithuania

Abstract: Two toponymical maps presented in this paper show 2332 inhabited places of Lithuania that have names (oikonyms) associated with vegetation and animals. The maps and the dataset are the outcomes of a project that is aimed at combining the outcomes of professional onomastic research with an environment that fosters exploration. The oikonyms were extracted from the reference base dataset of Lithuania by means of an automated algorithm. Original cartographic symbols have been designed for depicting categories and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Toponyms highlight the existence of bears as a natural ecological factor [116,117]. In Prahova Valley, the toponyms reflect the bear's habitat, with steep, rocky and rugged slopes [36,118] specific to the Bucegi Mountains.…”
Section: Toponyms and Souvenirs Attributes Of The Opportunism Of Tour...mentioning
confidence: 99%
“…Toponyms highlight the existence of bears as a natural ecological factor [116,117]. In Prahova Valley, the toponyms reflect the bear's habitat, with steep, rocky and rugged slopes [36,118] specific to the Bucegi Mountains.…”
Section: Toponyms and Souvenirs Attributes Of The Opportunism Of Tour...mentioning
confidence: 99%
“…Penggunaan istilah-istilah ini dalam menamai wilayah kelurahan/desa mencerminkan adanya keterkaitan dan saling pengaruh antara lingkungan alam dan bahasa. Istilah seperti ini sering disebut sebagai hydronym (Beconytė et al, 2019).Penggunaan toponimi yang dipengaruhi oleh faktor geografi fisik (abiotic) umumnya kata bermorfem tunggal atau monomorfemis dan kata bermorfem lebih dari satu atau polimorfemis sesuai penggunaan istilah geografi fisik tersebut dalam Bahasa asal (Hidayah, 2021).…”
Section: Gambar 4 Klasifikasi Menurut Unsur Biotik Dan Budayaunclassified
“…Numerous studies have found that historic toponyms provide environmental information that may enable researchers to reconstruct former distributions of species of flora and fauna (e.g., Aybes and Yalden 1995, Boisseau and Yalden 1998, García Latorre et al 2001, Webster 2001, Cox et al 2002, Moore 2002, Yalden 2002, Hough 2008, Sousa et al 2010, Evans et al 2012, Beconyte et al 2019) (Appendix S1).…”
Section: Introductionmentioning
confidence: 99%